1969
DOI: 10.1111/j.1476-5381.1969.tb08013.x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid potentiation of responses to sympathomimetic amines in aortic strips

Abstract: Hydrocortisone potentiates responses to adrenaline and noradrenaline in aortic strips by inhibiting their inactivation by catechol-O-methyl transferase (Kalsner, 1969). It was of interest to determine whether other steroid hormones also enhance responses to catecholamines and decrease their rate of inactivation by 0-methylation. In the present study the effects of 17f-oestradiol, progesterone and desoxycorticosterone on responses to a variety of sympathomimetic amines were investigated. MethodsRabbit aortic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

1977
1977
1994
1994

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 11 publications
5
61
1
Order By: Relevance
“…This is to be expected given that Iso is the preferred substrate for both extraneuronal uptake and for COMT (Gillespie, 1973;Guldberg & Marsden, 1975;Trendelenburg, 1980). Kalsner (1969) suggested that cortisol-induced potentiation of vascular responses to catecholamines may be due to inhibition of COMT or extraneuronal uptake. This steroid was shown to inhibit both COMT and uptake in cat heart (Cornish & Goldie, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is to be expected given that Iso is the preferred substrate for both extraneuronal uptake and for COMT (Gillespie, 1973;Guldberg & Marsden, 1975;Trendelenburg, 1980). Kalsner (1969) suggested that cortisol-induced potentiation of vascular responses to catecholamines may be due to inhibition of COMT or extraneuronal uptake. This steroid was shown to inhibit both COMT and uptake in cat heart (Cornish & Goldie, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…17,B-Oestradiol, progesterone, testosterone, corticosterone, deoxycorticosterone and cortisol-HS are potent inhibitors of extraneuronal catecholamine uptake (Kalsner, 1969;Salt, 1972;Cornish etal., 1978) Of these steroids, only 17p-oestradiol is known also to inhibit the neuronal uptake of catecholamines (Iversen & Salt, 1970;Salt, 1972;Cornish et al, 1978). Normetanephrine (4-22 ElM) is known to inhibit selectively extraneuronal uptake by approximately 50% (Burgen & Iversen, 1965;Mireyless & Foster, 1973;Major, Sauerwein & Graefe, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quintana (1977) suggested that the steroidal structure of pancuronium might confer some of the properties exhibited by the corticosteroids and some of their derivatives. These drugs promote an acute NA supersensitivity in cardiac and arterial smooth muscle, 17 ,B-oestradiol being the most potent (see, for instance Kalsner, 1969;Iversen & Salt, 1970). However, it is interesting that the response of the rat vas deferens to corticosteroids is atypical; 17 P-oestradiol is a potent non-competitive antagonist of NA on this preparation (Tomlinson unpublished).…”
Section: Interactions Between Pancuronium and Cocainementioning
confidence: 99%